A 22-Year-Old Woman With Eisenmenger Due to Atrial Septal Defect; A Case Report - Katharina, Elva; Jonathan, Steven; Meuraxa, M. Iqbal; Karlina, Jevanlia; Sipayung, Helni (Peneliti.net, 2024)
Atrial septal defects (ASDs) constitute a common form of congenital heart defect (CHD) and can lead to significant morbidity and mortality in adulthood if left untreated. While advancements in prenatal screening and fetal echocardiography have facilitated early interventions, some cases may go undetected until adulthood, manifesting as symptoms like progressive shortness of breath. A recent case involved a 22-year-old woman with a history of ASD since childhood, presenting with cyanosis, digital clubbing, and peripheral edema. Examination revealed cardiomegaly, right atrial enlargement, and right ventricular hypertrophy. Diagnostic tests, including chest X-ray, electrocardiogram, and echocardiography, confirmed features consistent with Eisenmenger's syndrome, characterized by severe pulmonary hypertension and a large secundum ASD. Effective management requires a multidisciplinary approach involving cardiologists, pulmonologists, cardiac surgeons, and internists. It is crucial to address the underlying causes, as medications targeting pulmonary vessels may not consistently provide reliable results. Timely intervention and collaboration among specialists are paramount in improving outcomes for individuals with ASDs and preventing complications associated with Eisenmenger's syndrome